Organic / inorganic hybridized carbonized polymer dot film layer with high refractive index and preparation method of organic / inorganic hybridized carbonized polymer dot film layer
Through the preparation of the carbonized polymer dot film layer, the problem of traditional inorganic nanoparticles agglomeration in polymer matrix is solved, and the carbonized polymer dot film layer with high refractive index and good compatibility is achieved, which improves the performance of optoelectronic devices and Processing performance.
Patent Information
- Application Number
- CN202411217278.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-02
AI Technical Summary
Traditional inorganic nanoparticles are prone to agglomeration in polymer matrix, resulting in poor refractive index regulation, poor processing performance and deterioration of toughness, making it difficult to meet the design requirements of high-performance optoelectronic devices.
Carbonated polymer dots (CPDs) are used as organic/inorganic hybrid materials, and high refractive index CPDs are prepared by solvothermal method, and a high refractive index carbonated polymer dot film layer is formed through the thermal curing process to overcome the problem of nanoparticle agglomeration and improve the material refractive index and compatibility.
The carbonized polymer dot film layer with high refractive index, stable structure, easy to modify and composite is achieved, which improves the performance and processing performance of optoelectronic devices and is suitable for the preparation of optical and electronic devices.
Smart Images

Figure CN119119822A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-refractive-index nanoparticle preparation, and in particular relates to an organic / inorganic hybrid high-refractive-index carbonized polymer dot film layer and a preparation method thereof. Background Art
[0002] With the development of science and technology, instruments and equipment are developing towards intelligence, integration and miniaturization. Correspondingly, the performance of components in instruments needs to be further improved to meet application requirements. High refractive index materials are the key to the preparation of high-performance optical and electronic devices. They have been widely used in the preparation of high-performance optical components such as optical adhesives, nanoimprinting, 1D photonic crystals, optical waveguides, microlens arrays, and holographic optical elements. High refractive index materials in high-performance optoelectronic devices must meet design requirements such as precise adjustment of refractive index, excellent processing performance, light texture and low cost. Although traditional inorganic materials have a high refractive index (such as ZnO2~2.10, ZnS~2.37, TiO2~2.61), high mechanical strength and heat resistance, they have the disadvantages of poor refractive index controllability, poor processing performance and high density, which makes it difficult to meet the design requirements of high-performance optoelectronic devices. Organic polymers have the characteristics of simple molding and processing, light texture, impact resistance and low cost. The high refractive index inorganic nanoparticle-polymer composites prepared by preparing inorganic high refractive index materials into nanoparticles and compounding them with organic polymers are currently an important development direction of high refractive index materials. The main difficulty in preparing inorganic nanoparticle hybrid high refractive index polymer materials is how to inhibit the agglomeration of nanoparticles with high surface energy and increase their doping amount in the polymer matrix. The commonly used method is to modify small molecules or polymer chains on the surface of inorganic nanoparticles to inhibit the aggregation of nanoparticles, but the introduction of surface modifiers will reduce the refractive index of nanoparticles to a certain extent. At the same time, when the doping amount increases, the toughness of the composite material will decrease significantly. Therefore, it is urgent to develop a new type of nanoparticles with high refractive index properties and good compatibility with polymers.
[0003] Carbonized polymer dots (CPDs) are a new type of organic / inorganic hybrid zero-dimensional carbon-based nanomaterials. Their structure consists of a highly cross-linked or slightly graphitized core and a polymer chain shell with rich functional groups. They can be generated from precursors such as small molecules, polymers or biomass through polymerization, cross-linking and carbonization. During the synthesis, the precursor raw materials are designed to introduce high molar refractive index groups or atoms, and the CPDs nanostructure is controlled by controlling the reaction conditions. The degree of cross-linking carbonization at the nanoscale inside the CPDs is increased to increase the refractive index of the material. Since the surface of CPDs has rich functional groups or short polymer chains, it is easy to compound with polymer materials. The unique "core-shell" structure of CPDs provides a new research direction for the synthesis of high refractive index materials. Summary of the invention
[0004] The purpose of the present invention is to prepare an organic / inorganic hybrid high refractive index carbonized polymer dot film layer based on carbonized polymer dots, which has the advantages of high refractive index, easy synthesis, stable structure, easy modification and compounding, and can overcome the problem that traditional inorganic nanoparticles are easy to agglomerate in the polymer matrix.
[0005] The method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer of the present invention comprises the following steps:
[0006] (1) Preparation of high refractive index CPDs by solvothermal method
[0007] Weigh an aldehyde-containing aromatic compound and a hydroxyl- or thiol-containing aromatic compound in a molar ratio of aldehyde group to hydroxyl group or thiol group of 1:0.25-4 and dissolve them in a solvent, and the mass ratio of the sum of the aldehyde-containing aromatic compound and the hydroxyl- or thiol-containing aromatic compound to the solvent is 1:5-30; then add an acid catalyst in a molar ratio of 0.05-0.4:1 to the aldehyde-containing aromatic compound, and ultrasonically vibrate to completely dissolve the aldehyde-containing aromatic compound and the hydroxyl- or thiol-containing aromatic compound; then transfer to a stainless steel reactor lined with polytetrafluoroethylene, and perform a solvent thermal reaction at a certain temperature. The reaction process using terephthalaldehyde and 4,4-dimercaptodiphenyl sulfide as raw materials is shown in Formula 1; after the reaction is completed, filter and remove insoluble matter using a 0.22 micron filter head, and drop the filtrate into a reverse precipitant for reverse precipitation operation, and use 10-50 mL of reverse precipitant for reverse precipitation for every 10 mL of filtrate, and obtain a high refractive index CPDs viscous solid after centrifugation;
[0008]
[0009] (2) Preparation of film curing liquid
[0010] Dissolving 1 part by weight of the high refractive index CPDs viscous solid obtained in step (1) in 10 to 20 parts by weight of a solvent, and obtaining a film layer solidification liquid after uniform dissolution;
[0011] (3) Preparation of high refractive index carbonized polymer dot film layer by thermal curing of high refractive index carbonized polymer dots
[0012] The film curing liquid obtained in step (2) is applied to the substrate, and after heating and curing at a certain temperature, a high refractive index carbonized polymer dot film layer with a thickness of 5 to 60 μm is obtained; since there are still unreacted groups on the polymer chain on the surface of the prepared high refractive index carbonized polymer dot film layer, these groups will further react during the thermal curing process to make the film layer thermosetting. The reaction process is as follows: Figure 4 As shown;
[0013] The aldehyde-containing aromatic compound in step (1) is one or a mixture of benzaldehyde (A), o-phthalaldehyde (B), isophthalaldehyde (C), terephthalaldehyde (D), trimesic acid (E), 1-naphthaldehyde (F), 1,6'-naphthalenedicarbaldehyde (G), 1,4'-naphthalenedicarbaldehyde (H), 4,4'-biphenylcarboxaldehyde (I), thiophene-2,5-dicarboxaldehyde (J), and thieno[3,2-b]thiophene-2,5-dicarboxaldehyde (K); the hydroxyl- or thiol-containing aromatic compound is one or a mixture of 2,2'-dihydroxybiphenyl (L), 4,4'-dihydroxydiphenylmethane (M), 4,4'-dihydroxydiphenyl sulfide (N), bis(4-hydroxyphenyl) disulfide (O), phenylenediol (P), and 4,4'-dimercaptodiphenyl sulfide (Q), and the structural formula is shown in Formula 2.
[0014]
[0015] Preferably, the solvent in step (1) is one or a mixture of 1,4-dioxane, 1,3-dioxane, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide.
[0016] Preferably, the acidic catalyst in step (1) is one or a mixture of hydrochloric acid (12 mol / L), p-toluenesulfonic acid, trifluoroacetic acid, and zirconium tetrachloride.
[0017] Preferably, the temperature of the solvent thermal reaction in step (1) is 140 to 240° C., and the reaction time is 4 to 16 hours.
[0018] Preferably, the deprecipitant prepared in step (1) is a mixed solution of n-hexane and ethyl acetate, and the volume ratio of ethyl acetate to n-hexane is 1:1-5.
[0019] Preferably, the solvent in step (2) is one or a mixture of 1,4-dioxane, 1,3-dioxane, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide.
[0020] Preferably, the substrate in step (3) is glass, polycarbonate or polyethylene terephthalate, and the surface of the substrate needs to be cleaned with anhydrous ethanol before use to remove dust and other attachments, and no other treatment is required.
[0021] Preferably, in step (3), curing is performed at 40 to 140° C. for 1 to 8 hours.
[0022] The high refractive index carbonized polymer dot film layer prepared by the present invention has a high refractive index and is easy to mold and process. An anti-reflection coating can be prepared by preparing film layers with different refractive index gradients to increase the visible light transmittance of the substrate, which can be used to improve the light extraction efficiency of OLEDs; or a high refractive index carbonized polymer dot film layer and a low refractive index polymer are stacked to prepare a Bragg reflector, and a high reflectivity of light in a specific band can be achieved by controlling the thickness of the stacking layer, which can be applied to colorful structural color anti-counterfeiting coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : Infrared characterization spectrum of the surface state of CPDs-1 prepared in Example 1;
[0024] Figure 2 : Elemental composition analysis spectrum of CPDs-3 prepared in Example 3;
[0025] Figure 3 : Transmission electron microscopy photograph of CPDs-4 prepared in Example 4;
[0026] Figure 4 :Schematic diagram of the process of preparing high refractive index film layer by thermal curing of high refractive index carbonized polymer dots;
[0027] Table 1: Experimental data of the film layers of various embodiments
[0028] Film CPDs particle size Film thickness Transmittance (550nm) Refractive index (589nm) Film layer-1-1 3.21nm 5.1μm 91.13% 1.7764 Film layer-1-2 3.21nm 11.4μm 87.23% 1.7791 Film layer-1-3 3.21nm 59.6μm 81.31% 1.7810 Film layer-2 2.68nm 10.2μm 90.36% 1.7064 Film layer-3 4.71nm 12.3μm 75.48% 1.8023 Film layer-4 4.93nm 13.4μm 83.29% 1.8237
[0029] As can be seen from Table 1, the film layer prepared by high refractive index carbonized polymer dots has a higher refractive index, and the sulfur-carbon-sulfur structure generated by the acetal reaction makes the film layer have excellent visible light transmittance. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0031] Example 1
[0032] Weigh 147 mg of terephthalaldehyde and 630.7 mg of 4,4'-dimercaptodiphenyl sulfide and dissolve them in 15 g of 1,4'-dioxane, then add 30 mg of 12 mol / L hydrochloric acid; ultrasonically oscillate to completely dissolve terephthalaldehyde and 4,4'-dimercaptodiphenyl sulfide, then transfer to a 25 mL stainless steel reactor lined with polytetrafluoroethylene, and react at 160°C for 15 hours. After the reaction, use a 0.22 micron filter to filter out insoluble matter, take 15 mL of the filtrate and add it to 40 mL of a reverse precipitant (1:1 volume ratio of ethyl acetate to n-hexane) for reverse precipitation, and centrifuge the solution to obtain 511 mg of high refractive index CPDs-1. Figure 1 As shown, 2480~2577cm -1 and 1666~1734cm -1 The infrared absorption at 400 nm proved that there were unreacted thiol and aldehyde groups on the surface of CPDs-1, which was conducive to the further dehydration condensation and curing of CPDs-1 into film.
[0033] 100 mg CPDs-1 was dissolved in 1.2 g 1,4'-dioxane, and the film layer solidification liquid was obtained after uniform dissolution. 40 μL of the solidification liquid was applied to a glass substrate (the surface of the glass substrate was wiped with anhydrous ethanol before use to remove dust and other attachments), and cured at 60°C for 2 hours to obtain a 5.1 μm thick CPDs-1-based high refractive index transparent film layer, which was recorded as film layer-1-1. The properties of film layer-1-1 are shown in Table 1.
[0034] 100 μL of the curing solution was applied to a glass substrate and cured at 60°C for 3 hours to obtain a 11.4 μm thick CPDs-1-based high refractive index transparent film layer, which was recorded as film layer-1-2. The properties of film layer-1-2 are shown in Table 1.
[0035] 700 μL of the curing solution was applied to a glass substrate and cured at 80°C for 6 hours to obtain a 59.6 μm thick CPDs-1-based high refractive index transparent film layer, which was recorded as film layer-1-3. The properties of film layer-1-3 are shown in Table 1.
[0036] like Figure 4 As shown, the coating curing liquid is scraped onto the substrate, and after heating at a certain temperature to volatilize the solvent and curing for a period of time, a high-refractive index transparent film layer prepared by carbonized polymer dots is obtained. Since there are unreacted aldehyde groups and thiol groups on the surface of the prepared high-refractive index carbonized polymer dots, the aldehyde groups and thiol groups will further dehydrate and condense to form a cross-linked structure during the heating process. At the same time, the polymer chains on the surface of the high-refractive index carbonized polymer dots will be entangled during the evaporation of the solvent, further promoting the formation of the film layer.
[0037] The film solidification liquid prepared by CPDs-1 and low-refractive index polymethyl methacrylate (PMMA) were alternately spin-coated into a laminated structure to prepare a Bragg reflector. The thickness of the single-layer CPDs-1 film layer and the single-layer PMMA layer in the laminated structure are 72nm and 83nm respectively. The refractive index of the CPDs-1 film layer is 1.7791, which is a high-refractive index phase; the refractive index of PMMA is 1.49, which is a low-refractive index phase; in the laminated structure, the high-refractive index phase and the low-refractive index phase are alternately spin-coated 10 layers respectively. Due to the appropriate thickness and large difference in refractive index, the Bragg reflector can specifically reflect light in the 483-501nm band, with a reflectivity of 80%.
[0038] Example 2
[0039] Weigh 241 mg of trimesaldehyde, 212 mg of 2,2'-dihydroxybiphenyl and 421 mg of 4,4'-dihydroxydiphenylmethane and dissolve them in 11 g of tetrahydrofuran, then add 30 mg of trifluoroacetic acid; transfer to a 25 mL stainless steel reactor lined with polytetrafluoroethylene after ultrasonic vibration until the solid is completely dissolved, and react at 200°C for 8 hours. After the reaction, use a 0.22 μm filter to filter out insoluble matter, take 10 mL of the filtrate and add 40 mL of a reverse precipitant (ethyl acetate to n-hexane in a volume ratio of 1:5) for reverse precipitation, and centrifuge the solution to obtain 632 mg of high refractive index CPDs-2.
[0040] 100 mg of CPDs-2 was dissolved in 1.3 g of 1,3'-dioxane, and the film layer solidification liquid was obtained after uniform dissolution. 100 μL of the solidification liquid was applied to a polyethylene terephthalate substrate and cured at 80°C for 2 hours to obtain a CPDs-2-based high refractive index transparent film layer, which was recorded as film layer-2. The properties of film layer-2 are shown in Table 1. Due to the lack of sulfur doping, the refractive index value of film layer-2 is relatively low.
[0041] Example 3
[0042] Weigh 432 mg of 1,6'-naphthalene dicarboxaldehyde, 109 mg of 4,4'-biphenyl dicarboxaldehyde, 378 mg of 4,4'-dihydroxydiphenyl sulfide and 235 mg of bis(4-hydroxyphenyl) disulfide and dissolve them in 22 g of tetrahydrofuran, then add 40 mg of p-toluenesulfonic acid; transfer to a 50 mL stainless steel reactor lined with polytetrafluoroethylene after ultrasonic vibration until the solid is completely dissolved, and react at 240°C for 10 hours. After the reaction, filter with a 0.22 micron filter to remove insoluble matter. Considering the change in product polarity corresponding to the change in precursor raw materials, take 15 mL of filtrate and add 40 mL of reverse precipitant (1:3 volume ratio of ethyl acetate to n-hexane) for reverse precipitation. Centrifuge the solution to obtain 836 mg of high refractive index CPDs-3. Figure 2As shown, by controlling the precursor raw materials, sulfur element was successfully hybridized into CPDs-3.
[0043] 100 mg of CPDs-3 was dissolved in 1.1 g of tetrahydrofuran and uniformly dissolved to obtain a film layer solidification liquid. 100 μL of the solidification liquid was applied to a polycarbonate substrate and cured at 120°C for 6 hours to obtain a CPDs-3-based high refractive index transparent film layer, which was recorded as film layer-3. Due to the presence of disulfide bonds, the transmittance of film layer-3 in the visible light region decreased, and the properties of film layer-3 are shown in Table 1.
[0044] Example 4
[0045] By increasing the sulfur content in the system, the refractive index of the film layer was further improved. 329 mg of thiophene-2,5-dicarboxaldehyde, 276 mg of thieno[3,2-b]thiophene-2,5-dicarboxaldehyde, 557 mg of phenylenediol and 371 mg of 4,4'-dimercaptodiphenyl sulfide were weighed and dissolved in a mixed solution of 22 g of N-methylpyrrolidone and N,N-dimethylacetamide (the masses of the two were 11 g respectively), and then 60 mg of zirconium tetrachloride was added; after ultrasonic vibration until the solid was completely dissolved, it was transferred to a 50 mL stainless steel reactor lined with polytetrafluoroethylene and reacted at 220°C for 8 hours. After the reaction, the insoluble matter was filtered out using a 0.22 micron filter head. Considering the change in product polarity corresponding to the change in the precursor raw material, 20 mL of the filtrate was added to 40 mL of a reverse precipitant (the volume ratio of ethyl acetate to n-hexane was 1:2) for reverse precipitation. After the solution was centrifuged, 964 mg of high refractive index CPDs-4 was obtained. Figure 3 As shown, CPDs-4 has a small particle size and is evenly distributed.
[0046] 100 mg of CPDs-4 was dissolved in 1.4 g of N-methylpyrrolidone and uniformly dissolved to obtain a film layer solidification liquid. 100 μL of the solidification liquid was applied to a polycarbonate substrate and cured at 80°C for 8 hours to obtain a CPDs-4-based high refractive index transparent film layer, which was recorded as film layer-4. Due to the increase in sulfur content, the visible light transmittance of film layer-4 was not high, but the refractive index of the film layer was significantly improved. The properties of film layer-4 are shown in Table 1.
[0047] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general method used herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer, the steps of which are as follows: (1) Preparation of high refractive index CPDs by solvothermal method Weigh an aldehyde-containing aromatic compound and a hydroxyl- or thiol-containing aromatic compound in a molar ratio of aldehyde group to hydroxyl group or thiol group of 1:0.25-4, dissolve them in a solvent, and the mass ratio of the sum of the aldehyde-containing aromatic compound and the hydroxyl- or thiol-containing aromatic compound to the solvent is 1:5-30; then add an acid catalyst in a molar ratio of 0.05-0.4:1 to the aldehyde-containing aromatic compound, and ultrasonically vibrate to completely dissolve the aldehyde-containing aromatic compound and the hydroxyl- or thiol-containing aromatic compound; then transfer to a stainless steel reactor lined with polytetrafluoroethylene, and perform a solvent thermal reaction at a certain temperature; after the reaction is completed, use a 0.22 micron filter head to filter and remove insoluble matter, and drop the filtrate into a reverse precipitant for reverse precipitation operation, and use 10-50 mL of reverse precipitant for every 10 mL of filtrate for reverse precipitation, and obtain a high refractive index CPDs viscous solid after centrifugation; (2) Preparation of film curing liquid Dissolving 1 part by weight of the high refractive index CPDs viscous solid obtained in step (1) in 10 to 20 parts by weight of a solvent, and obtaining a film layer solidification liquid after uniform dissolution; (3) Preparation of high refractive index carbonized polymer dot film layer by thermal curing of high refractive index carbonized polymer dots The film layer solidifying liquid obtained in step (2) is applied on the substrate, and after heating and solidification at a certain temperature, a high refractive index carbonized polymer dot film layer with a thickness of 5 to 60 microns is obtained.
2. The method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer according to claim 1, characterized in that: The aldehyde-containing aromatic compound in step (1) is one or a mixture of benzaldehyde, o-phthalaldehyde, isophthalaldehyde, terephthalaldehyde, trimesic acid, 1-naphthaldehyde, 1,6'-naphthalenedicarbaldehyde, 1,4'-naphthalenedicarbaldehyde, 4,4'-biphenylcarboxaldehyde, thiophene-2,5-dicarboxaldehyde, and thieno[3,2-b]thiophene-2,5-dicarboxaldehyde; the hydroxyl- or thiol-containing aromatic compound is one or a mixture of 2,2'-dihydroxybiphenyl, 4,4'-dihydroxydiphenylmethane, 4,4'-dihydroxydiphenyl sulfide, bis(4-hydroxyphenyl)disulfide, phenylenediol, and 4,4'-dimercaptodiphenyl sulfide.
3. The method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer according to claim 1, characterized in that: The solvent in step (1) is one or a mixture of 1,4-dioxane, 1,3-dioxane, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
4. The method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer according to claim 1, characterized in that: The acidic catalyst in step (1) is one or a mixture of hydrochloric acid, p-toluenesulfonic acid, trifluoroacetic acid, and zirconium tetrachloride.
5. The method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer according to claim 1, characterized in that: The temperature of the solvent thermal reaction in step (1) is 140 to 240° C., and the reaction time is 4 to 16 hours.
6. The method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer according to claim 1, characterized in that: The anti-precipitant prepared in step (1) is a mixed solution of n-hexane and ethyl acetate, and the volume ratio of ethyl acetate to n-hexane is 1:1-5.
7. The method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer according to claim 1, characterized in that: The solvent in step (2) is one or a mixture of 1,4-dioxane, 1,3-dioxane, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
8. The method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer according to claim 1, characterized in that: The substrate in step (3) is glass, polycarbonate or polyethylene terephthalate. Before use, the surface of the substrate needs to be cleaned with anhydrous ethanol to remove dust and other attachments. No other treatment is required.
9. The method for preparing an organic / inorganic hybrid high refractive index carbonized polymer dot film layer according to claim 1, characterized in that: In step (3), the curing is carried out at 40 to 140° C. for 1 to 8 hours.
10. An organic / inorganic hybrid high refractive index carbonized polymer dot film layer, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Transparent high-refractivity graphene quantum-dot / polymer nano composite film and preparation method thereof
CN102643501A
Photodiffusion functional coating material and preparation method thereof
CN108864802A
Brain drug delivery system for breaking through blood brain barrier through carbonized polymer dots and ginkgolide B
CN113081974A
P heteroatom-containing multi-element sulfhydryl compound, LED (light-emitting diode) organic silicon packaging material and preparation method of LED organic silicon packaging material
CN116640166A
The process for obtaining of fluoralkylated carbon quantum dots
WO2020121119A1
Cited By
Reusable optical adhesive with high refractive index and preparation method thereof
CN121227276A
Flame-retardant TPEE material as well as preparation method and application thereof
CN121851635A
